Epiphytic orchids of Nepal - Ghimire, M (Banko Janakari, 2009)
This paper includes a list of 207 species of epiphytic orchids from Nepal that belong to 49 genera including 5 endemic species (Bulbophyllum ambrosia, Eria baniai, E. nepalensis, Oberonia nepalensis and Pleione coronaria). Phytogeographical distribution along with altitudinal ranges of all of these epiphytic species, phenology of flowering of 199 species and host plant(s) of 148 species have been reported herewith. The aim of this paper is to assess the distribution patterns, host-epiphyte relationship and phenology of flowering of Nepalese epiphytic orchids. Key words: Epiphytic orchids, host range, phenology, Nepal doi: 10.3126/banko.v18i2.2173 Banko Janakari, Vol. 18, No. 2, 53-63